2019
DOI: 10.1097/mjt.0000000000001098
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Nonopioids Versus Opioids for Acute Pain in the Emergency Department: A Literature Review

Abstract: Background: Pain is the most common reason for patient visits in the emergency department (ED). Opioids have been long considered the standard of care for acute pain in the ED. Because of the opioid crisis, investigation and implementation of novel practices to manage pain is needed. The use of various nonopioids has been suggested as a plausible alternative to opioids, with emerging literature to support its use for acute pain in the ED. Study Question: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We considered the possibility of abdominal pain as a manifestation of depression and depression as a consequence of unremitting abdominal pain. The ongoing opioid epidemic in the United States, as well as clinical experience and studies noting frequent opioid prescribing in the ED setting of recurrent abdominal pain, prompted consideration of opioid use disorder screening and alternative methods of pain control 3,17–26,28–30,78–86 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered the possibility of abdominal pain as a manifestation of depression and depression as a consequence of unremitting abdominal pain. The ongoing opioid epidemic in the United States, as well as clinical experience and studies noting frequent opioid prescribing in the ED setting of recurrent abdominal pain, prompted consideration of opioid use disorder screening and alternative methods of pain control 3,17–26,28–30,78–86 …”
Section: Methodsmentioning
confidence: 99%
“…The ongoing opioid epidemic in the United States, as well as clinical experience and studies noting frequent opioid prescribing in the ED setting of recurrent abdominal pain, prompted consideration of opioid use disorder screening and alternative methods of pain co ntrol. 3,[17][18][19][20][21][22][23][24][25][26][28][29][30][78][79][80][81][82][83][84][85][86] An important consideration for the GRACE-2 writing group was the feasibility of the guideline for physicians and patients in various practice settings. We debated including recommendations for testing for conditions such as Helicobacter pylori but noted that some forms of testing such as exhaled carbon dioxide or immunological testing might not be available within an ED time frame in some settings.…”
Section: Selection Of Questionsmentioning
confidence: 99%
“…Others have found that opioids are not superior to NSAIDs or acetaminophen at reducing acute pain in a prehospital setting 25 . However, another literature review on musculoskeletal pain in the ED reported that “No interventions were more effective at decreasing pain intensity than opioids at 60 min.” 26 Furthermore, a prospective cohort study of ED patients discharged with an opioid prescription showed that patients using opioids were more likely to report pain relief than those using NSAIDs and/or acetaminophen 27 . Nonetheless, the study was observational, not controlled or randomized.…”
Section: Introductionmentioning
confidence: 99%